Modeling the Distinct Negative-Reinforcement Mechanisms Associated with Alcohol Misuse and Unhealthy Snacking. (12th May 2019) - Reaves, Danielle L.; Christiansen, Paul; Boyland, Emma J.; Halford, Jason C. G.; Llewellyn, Clare H.; Hardman, Charlotte A.
Abstract: Background: Negative personality characteristics have been implicated in promoting overconsumption of both alcohol and food. Furthermore, positive motivations (enhancement) and negative motivations (coping) may mediate the association between personality and alcohol or food (over)consumption. Objectives: This study hypothesized that i.) drinking to cope and ii.) eating to cope would mediate the association between hopelessness/anxiety sensitivity and hazardous drinking/unhealthy snacking, respectively, and iii.) eating and drinking to cope would represent separate strategies. Methods: Participants were recruited via opportunity sampling through university schemes, social media, email and web page advertisements. Questionnaires included the Alcohol Use Disorders Identification Test, Substance Use Risk Profile Scale, Modified Drinking Motives Questionnaire Short Form, Palatable Eating Motives Scale and Snack/Meal Food Intake Measure. Results: Participants were 198 undergraduates, weight-related research volunteers and the public (83% female; 90% university educated). The hypothesized structural model fit the data well. As predicted, there were significant indirect associations between negative personality characteristics, hazardous drinking and unhealthy snacking via coping; specifically, individuals higher in anxiety sensitivity/hopelessness used food or alcohol to cope which, in turn, significantly predicted unhealthy snacking, and hazardous drinking, respectively. Importantly, drinking and eating to cope represented outcome-specific strategies, indicated by no significant association between eating to cope and hazardous drinking, or between drinking to cope and snacking. Conclusions: This study demonstrates that coping motivations are critical to the relationship between negative personality characteristics and unhealthy behaviors and highlights the distinct negative-reinforcement pathways associated with hazardous drinking and unhealthy snacking in majority university-educated females from the UK.